Managing intrathecal administration of nusinersen in adolescents and adults with 5q-spinal muscular atrophy and previous spinal surgery - Rodrigo de Holanda Mendonça; Hermann dos Santos Fernandes; Rafael Barbéro Schimmelpfeng Pinto; Ciro Matsui Júnior; Graziela Jorge Polido; André Macedo Serafim da Silva; Luis Fernando Grossklauss; Umbertina Conti Reed; Edmar Zanoteli (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Spinal muscular atrophy (SMA) is a neurodegenerative disease of lower motor neurons associated with frequent occurrence of spinal deformity. Nusinersen is an antisense oligonucleotide that increases SMN protein level and is administrated by frequent intrathecal lumbar injections. Thus, spinal deformities and previous spinal surgery are important challenges for drug delivery in SMA. Objective: To report imaging methods used for Nusinersen injection in SMA patients. Methods: Nusinersen injection procedures in SMA types 2 and 3 patients who had previous spinal surgery were analyzed retrospectively to describe the imaging and puncture procedures, as well as the occurrence of complications. Results: Nine SMA patients (14 to 50 years old) underwent 57 lumbar punctures for nusinersen injection. Six patients had no interlaminar space available; in five of them, a transforaminal approach was used, and another one underwent a surgery to open a posterior bone window for the injections. Transforaminal puncture was performed using CT scan in three cases and fluoroscopy in the other two, with a similar success rate. One patient in the transforaminal group had post-procedure radiculitis, and another one had vagal reaction (hypotension). In three cases, with preserved interlaminar space, injections were performed by posterior interlaminar puncture, and only one adverse event was reported (post-puncture headache). Conclusion: In SMA patients with previous spinal surgery, the use of imaging-guided intervention is necessary for administering intrathecal nusinersen. Transforaminal technique is indicated in patients for whom the interlaminar space is not available, and injections should always be guided by either CT or fluoroscopy.